2020
DOI: 10.1123/ijsnem.2019-0347
|View full text |Cite
|
Sign up to set email alerts
|

Worth the Weight? Post Weigh-In Rapid Weight Gain is Not Related to Winning or Losing in Professional Mixed Martial Arts

Abstract: Body mass (BM) manipulation via rapid weight loss (RWL) and rapid weight gain (RWG) is a common practice among mixed martial art (MMA) athletes to ensure qualification for the division in which the athlete wishes to compete. Professional MMA competitors in California are required to weigh in twice: 24 hr prior to competition and immediately prior to the bout after they have typically engaged in RWG. In analyzing data from five MMA events sanctioned by the Californian State Athletic Commission, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 20 publications
4
23
0
2
Order By: Relevance
“…This result is supported by recent data from another research group who also found that MMA training load is only reduced in the week of the bout [17]. In addition to extreme 'weight cutting' seen in our cohort and MMA competitors in general [8,9], it is more likely that performance would have been impaired. Though we did not collect any direct performance data, evidence from boxing suggests that a taper of 10 days or fewer causes a reduction in combat sport performance until several days after competition [45].…”
Section: Plos Onesupporting
confidence: 89%
See 2 more Smart Citations
“…This result is supported by recent data from another research group who also found that MMA training load is only reduced in the week of the bout [17]. In addition to extreme 'weight cutting' seen in our cohort and MMA competitors in general [8,9], it is more likely that performance would have been impaired. Though we did not collect any direct performance data, evidence from boxing suggests that a taper of 10 days or fewer causes a reduction in combat sport performance until several days after competition [45].…”
Section: Plos Onesupporting
confidence: 89%
“…This apparent lack of a physiological response to solely technical training is especially relevant given that successful and unsuccessful participants may be distinguishable by their lower body force production [7]. The requirement of incorporating a multitude of potentially conflicting technical and physical focused training sessions, coupled with the requirement to "make weight" for competition [8,9], clearly highlights the challenge and importance of formulating a well-structured and periodised training plan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to UK BJJ competitors weighing-in upon arrival at the venue, they may either have up to 1-2 hours to recover from AWL/RWL, or only a few minutes. This contrasts to professional boxing and MMA where competitors weigh-in 24-30 hours prior to competition (Kirk et al, 2020;Langan-Evans et al, 2011). Post weigh-in recovery of muscle glycogen may potentially occur during the time provided in boxing and MMA, but little glycogen is likely to be recovered in the minutes/hours BJJ competitors are afforded (L. M. Burke, van Loon, & Hawley, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there appears to be little effect of AWL/RWL on winning or losing in striking inclusive sports (Daniele, Weinstein, Wallace, Palmieri, & Bianco, 2016;Kirk, Langan-Evans, & Morton, 2020;Reale, Cox, Slater, & Burke, 2017), there is some support for this practice being predictive of success in grappling only events (Reale, Cox, Slater, & Burke, 2016;Wroble & Moxley, 1998).…”
Section: Introductionmentioning
confidence: 99%